2019
DOI: 10.1111/jpi.12601
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes human oocyte maturation and early embryo development by enhancing clathrin‐mediated endocytosis

Abstract: Embryo development potential and reproductive clinical outcomes are all deeply rooted in oocyte maturation. Melatonin has been reported to promote oocyte maturation as an antioxidant in nonprimate species. Its antioxidative functions also help reduce plasma membrane rigidity, which facilitates clathrin‐mediated endocytosis (CME). Whether melatonin has effects on human oocyte maturation by regulating CME is worthy of exploration. In this study, we found that the optimal melatonin concentration for human oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 49 publications
(91 reference statements)
1
28
0
Order By: Relevance
“…It is thought that many effects on embryonic development and clinical outcomes are deeply rooted in the oocyte maturation process 36 . However, because of suboptimal culturing conditions, IVM oocytes have been reported to exhibit embryonic developmental arrest at various stages 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that many effects on embryonic development and clinical outcomes are deeply rooted in the oocyte maturation process 36 . However, because of suboptimal culturing conditions, IVM oocytes have been reported to exhibit embryonic developmental arrest at various stages 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin and its metabolites are potent free radical scavengers and antioxidants in many organisms . It has been reported that MT can improve oocyte maturation in vitro and promote early embryo development in an animal model and even in humans; however, there is insufficient information on whether MT improves the developmental potential of immature human oocytes collected from the COH cycle and on the mechanisms of the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, MT was identified as a hormone primarily involved in the regulation of circadian rhythms of various physiological and neuroendocrine functions. However, MT has been recently shown to have multiple functions, especially in the reproductive system, by acting as a powerful free radical scavenger to protect the cells from oxidative stress damage, delay ovarian aging, regulate the production of progesterone, predict ovarian reserve, and in vitro fertilization (IVF) outcomes, as well as promote embryonic development …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During in vitro culture, melatonin (MT) has been reported to promote development of both fresh [38][39][40][41][42][43] and/or vitrified oocytes/embryos [10,42,[44][45][46], mainly by one or more events such as modulating the oxidative stress, improving mitochondrial function, regulating spindle assembly, chromosome arrangement and expression of key genes, and inhibiting the apoptosis. Previously we have also reported that MT supplementation during the whole length of experiment (warming, recovery, parthenogenetic activation, and embryo culture steps) might promote G1-to-S progression via regulation of ROS, GSH and expression of cell cycle-related genes, potentially increasing the parthenogenetic development ability of vitrified-warmed mouse oocytes [10,36].…”
Section: Introductionmentioning
confidence: 99%